Telaah Yuridis Terhadap Surat Edaran Kementrian Agraria Dan Tata Ruang No. 2/SE-HT.02.01/VI/2019 - Adhim, Nur; Mahmudah, Siti; Benuf, Kornelius (Jurnal Hukum & Pembangunan, 2020)
The Agraria Basic Law (UUPA) regulates that legal subjects for land rights, including land with HGB status (Right to Build), are Indonesian citizens and legal entities established under Indonesian law and domiciled in Indonesia. A different thing happened when a Circular from the Ministry of Agraria and Spatial Planning (ATR) was issued, stating that the Partnership Alliance (CV) could apply for land rights in the form of HGB. The difference in the substance of these rules will be analyzed using normative juridical writing methods, using secondary data. This paper will explain the legal status of CV in Indonesia, Arrangement of HGB acquisition in Indonesia so that later it will get a conclusion to answer the question of whether CV can have HGB in Indonesia.